Cyanoremediation and phyconanotechnology: cyanobacteria for metal biosorption toward a circular economy - Ciani, Matilde; Adessi, Alessandra (Frontiers in Microbiology, 2023)
Cyanobacteria are widespread phototrophic microorganisms that represent a promising biotechnological tool to satisfy current sustainability and circularity requirements. They are potential bio-factories of a wide range of compounds that can be exploited in several fields including bioremediation and nanotechnology sectors. The aim of this article is to illustrate the most recent trends in the use of cyanobacteria for heavy metals bioremoval (i.e. cyanoremediation) and metals recovery and reuse. Heavy metals biosorption by cyanobacteria can be combined with the consecutive valorization of the obtained metal-organic materials to get added-value compounds, including metal nanoparticles, opening the field of phyconanotechnology. Thus, the possibility to use combined approaches may help to increase the environmental and economic feasibility of the cyanobacteria-based processes promoting the transition towards a circular economy.